The adult males of Coccoidea (Hemiptera: Sternorrhyncha) known from Greenland - Hodgson, Chris (Zootaxa, 2005)
The males of nine of the 11 species of Coccoidea known from Greenland are described: 6 of species of Pseudococcidae (Atrococcus groenlandensis Gertsson & Hodgson, Chorizococcus multiporus Gertsson & Hodgson, Peliococcus balteatus (Green), Trionymus bocheri Gertsson & Hodgson, T. elymus Gertsson & Hodgson, and T. thulensis Green), 2 of species of Eriococcidae (Eriococcus munroi (Boratynski) and E. pseudinsignis Green), and one of Coccidae (Pulvinaria glacialis Gertsson & Hodgson). The question of their correct identification is discussed and a key is provided.